Chemical Composition, Insecticidal, Persistence and Detoxification Enzyme Inhibition Activities of Essential Oil of Artemisia maritima against the Pulse Beetle - Nandita Chauhan; Urvashi Kashyap; Shudh Kirti Dolma; Sajjalavarahalli G. Eswara Reddy (Molecules, 2022)
Pulse beetle is the major pests of pulses that cause significant loss to grains leads to unfit for consumption and marketing. Indiscriminate use of synthetic pesticides for the control of pulse beetle (Callosobruchus chinensis and Callosobruchus maculatus) led to insect resistance, pesticide residues on grains which affect consumer’s health and environment. Essential oils (EOs) are good alternatives to synthetics due to their safety to the environment and consumers’ health. The main objective of the present study was to explore the chemical composition, fumigant, repellency, ovipositional deterrence, persistence, and detoxification enzyme inhibition of Artemisia maritima essential oil against pulse beetle. Results showed that primary components of the EO were 1,8-Cineole and bornyl acetate. EO showed promising fumigant toxicity to C. chinensis and C. maculatus (LC50 = 1.17 and 0.56 mg/L, respectively) after 48 h. In the repellent assay, EO at 8 mg/L showed 92–96% repellence after 1 h. In ovipositional deterrence assay, EO showed more ovipositional deterrence against C. chinensis (OD50 = 3.30 mg/L) than C. maculatus (OD50 = 4.01 mg/L). Higher concentrations of oil (8 and 6 mg/L) in C. maculatus showed significant inhibition of the glutathione-S-transferase enzyme (7.14 and 5.61 n mol/min/mL, respectively).